Economic Benefits of Educating Girls In Developing Countries - Msuya, Nattu (Tanzania Journal for Population studies and Development, 2014)
The main objective of this paper is to uncover economic gains and society’s benefits when investing in girls’ education with the hope that the results will lead policy makers to reconsider the current underinvestment in girls. It explores the linkage between investing in girls and potential increase in national income by examining three widely prevalent aspects of adolescent girls’ lives: early school dropout, teenage pregnancy, and joblessness in Tanzania. Secondary data have been used for some comparability to allow for cross-country comparisons of the opportunity cost of investing on girls’ education. The data come from selected developing countries in Asia and Sub-Sahara Africa that have significant vulnerabilities for adolescent girls, or validating existing conditions aggravating adolescent girls’ social exclusion, which suggest a lower value for girl-children in the society. The findings reveal that investing in girls’ education leads to lifetime earning of today’s cohort of girls that is equivalent to 68% of annual domestic product. The cost of adolescent pregnancy as a share of gross domestic could be as high as 30% or low as 1% over a girl’s lifetime. The paper concludes that, as understanding grows about how much and how quickly education can result into tangible benefits for girls, their families and their countries, there is need to summon more political will and resources to provide girls and boys equal access to quality education.